A Guide to the Bayesian Analysis of Consumer Behavior Experiments With BANOVA Using Worked Examples. Issue 1 (February 2022) - Wedel, Michel; Kopyakova, Anna
This article provides a step-by-step guide for the analysis of experiments using Bayesian methods, using the BANOVA R package. We provide two worked examples. First, we reanalyze data from research by Romano and Balliet, which examined reciprocity and conformity as alternative mechanisms for cooperation between partners. The study has a between-subjects design and Poisson dependent variable, and we use Bayesian floodlight analysis to explore the interaction between reciprocity/conformity and two continuous covariates. Second, we reanalyze data from a study by Perfecto, Donnelly, and Critcher, who investigated whether mental simulation could be the psychological mechanism that explains how people make volume judgments of three-dimensional objects. The study has a mixed between- and within-subjects design with a Normal dependent variable, and we use Bayesian simple effects to explore the interactions between mental simulation and the shape and orientation of cups. The applications demonstrate the versatility of BANOVA (Bayesian Analysis of Variance) in analyzing a wide range of experimental designs and reveal that the results of the Bayesian analyses differ to some degree from those of the original studies.